2017
DOI: 10.1007/s12041-017-0808-5
|View full text |Cite
|
Sign up to set email alerts
|

The association study of nonsyndromic cleft lip with or without cleft palate identified risk variants of the $$\varvec{GLI3}$$ G L I 3 gene in a Chinese population

Abstract: Nonsyndromic cleft lip with or without cleft palate (NSCL/P) is a common birth defect due to abnormal orofacial development. Previous studies report abnormal sonic hedgehog (SHH) signalling activity during NSCL/P pathogenesis and propose several genes in the SHH pathway as candidate risk genes. As such, we focussed on GLI3, a downstream modulator of the SHH pathway. In the present study,we genotyped 34 tag SNPs covering GLI3 and performed association analysis with NSCL/P in 504 cases and 455 healthy controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Gli3 acts as an activator of hedgehog pathway targets in the presence of Shh signaling and becomes a repressor when Shh signaling is absent (Wang et al, 2000). Moreover, GLI3 has been associated with NSCLP in human patients (Wang et al, 2017b), and Gli3-null mouse embryos exhibit cleft palate and tongue abnormalities due to improper tongue morphogenesis and failure of palatal shelf elevation and fusion (Table 2, Fig. 3) (Huang et al, 2008).…”
Section: Wnt Signaling Crosstalk With Other Morphogenetic Signaling Pmentioning
confidence: 99%
“…Gli3 acts as an activator of hedgehog pathway targets in the presence of Shh signaling and becomes a repressor when Shh signaling is absent (Wang et al, 2000). Moreover, GLI3 has been associated with NSCLP in human patients (Wang et al, 2017b), and Gli3-null mouse embryos exhibit cleft palate and tongue abnormalities due to improper tongue morphogenesis and failure of palatal shelf elevation and fusion (Table 2, Fig. 3) (Huang et al, 2008).…”
Section: Wnt Signaling Crosstalk With Other Morphogenetic Signaling Pmentioning
confidence: 99%
“…Shh signaling also fine-tunes limb patterning ( Johnson et al, 1994 ) and craniofacial development ( Xavier et al, 2016 ) during early fetal life. Therefore, the abnormal regulation of Shh signaling secondary to genetic mutations in the mouse and human results in various congenital malformations, such as neural tube defects (NTDs) ( Wu et al, 2013 ; Lu et al, 2014 ; Kim et al, 2019 ; Renard et al, 2019 ), abnormal brain development ( Dhekne et al, 2018 ; Nagai-Tanima et al, 2020 ), craniofacial abnormalities ( Xavier et al, 2016 ; De Mori et al, 2017 ; Wang et al, 2017 ), and limbs defects ( Anderson et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the association between icTeV and genetic factors have identified several causative gene families and genes, including Hox (10,11), caspase (2,11), paired like homeodomain 1 (7)(8)(9)12), T-box transcription factors and Gli family zinc finger 3 (10,13) genes. However, a major candidate gene remains to be identified (5).…”
Section: Introductionmentioning
confidence: 99%